Bantuan Luar Negeri dan Pembangunan Desa: Efektivitas Participatory Irrigation Sector Project (PISP) di Desa Sumber Pucung, Kabupaten Malang - Al Akbar, Muhammad Fandiaz; Setiawan, Arief (Jurnal Transformasi Global, 2020)
This research examines the effectiveness of HIPPA (Himpunan Petani Pemakai Air) in Sumberpucung Village, Malang Regency, after the implementation of PISP (Participatory Irrigation Sector Project) funded by ADB and the Dutch Government. The effectiveness will be measure through participation or a participatory approach. This research finds that a low level of participation in the HIPPA organization is due to power, structure, and individual motivations. The results of this research are the stagnancy of the HIPPA organization as a medium for participatory irrigation projects in the village.